SOSIALISASI TERHADAP SPESIES IKAN YANG DILINDUNGI DI DUSUN WAIYOHO DESA KAWA - Laole Laole; Hartono Nurlette (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The marine and fishery sector is one of the leading sectors and the main driving force that builds the regional economy of the Maluku province, especially in the provision of protein feed ingredients and can improve the welfare of the community, especially fishermen groups, most of whom live in coastal areas. The purpose of this community service activity is to socialize protected fish species for tuna fishing communities. This community service activity was carried out on December 24-25 2022. Community service activity being carried out in the Waiyoho Kawa Village, West Seram Regency. Implementation of activities through several stages, namely: location survey, in-depth interviews, outreach and evaluation. The results of community service can increase the knowledge and insight of tuna fishermen in Waiyoho about protected fish species. The material explained includes (1) 20 protected fish species, (2) the importance of diversity of fish species, (3) sustainable use of fish resources